Developing adapter for importing data from external sources - M. V. Sterjanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
HP DDM allows to monitor the changes in IT-infrastructure without installing any third-party components in destination network. In this article, development adapter for making import from external sources is described. Practical value is that UCMDB input costs go down because of using automated approach for data import from multiple external data sources preserving dependencies.